Estimating the likelihood of significant climate change with the NCAR 40-member ensemble - Foust, William Eliott, author; Thompson, David, advisor; Randall, David, committee member; Barnes, Elizabeth, committee member; Cooley, Daniel, committee member (Colorado State University. Libraries, 2014)
Increasing greenhouse gas concentrations are changing the radiative forcing on the climate system, and this forcing will be the key driver of climate change over the 21st century. One of the most pressing questions associated with climate change is whether certain aspects of the climate system will change significantly. Climate ensembles are often used to estimate the probability of significant climate change, but they struggle to produce accurate estimates of significant climate change because they sometimes require more realizations than what is feasible to produce. Additionally, the ensemble mean suggests how the climate will respond to an external forcing, but since it filters out the variability, it cannot determine if the response is significant. In this study, the NCAR CCSM 40-member ensemble and a lag-1 autoregressive model (AR1 model) are used to estimate the likelihood that climate trends will be significant. The AR1 model generates an analytic solution for what the distribution of trends should be if the NCAR model was run an infinite number of times. The analytical solution produced by the AR1 model is used to assess the significance of future climate trends. The results of this study demonstrate that an AR1 model can aid in making a probabilistic forecast. Additionally, the results give insight into the certainty of the trends in the surface temperature field, precipitation field, and atmospheric circulation, the probability of climate trends being significant, and whether the significance of climate trends is dependent on the internal variability or anthropogenic forcing.
Keywords: climate; uncertainty; significance